Game Theory as a Marketing Optimization Tool: A Case Study on Kelom Geulis - Azahra, Astrid Sulistya; Saefullah, Rifki; Wahid, Alim Jaizul (iora, 2024)
Competition in the market for traditional art products, such as Kelom Geulis, has become increasingly intense along with the growing public interest in aesthetically and culturally valuable items. This competition forces producers to develop effective marketing strategies to maintain their competitiveness. This study adopts a game theory approach to evaluate and formulate optimal marketing strategies between two major producers. The research method involves the use of questionnaires covering three main aspects: improving product quality, setting competitive prices, and enhancing customer service. Data analysis is conducted using a payoff matrix to determine the best strategies that can increase profits or reduce losses for each party.The results show that a saddle point is reached at a value of 4.57, where PT A achieves a profit increase from 4 to 4.57, while PT B reduces its loss from 6 to 4.57. This optimal strategy can be achieved if PT A prioritizes improving product quality and setting competitive prices, while PT B A prioritizes setting competitive prices and service quality enhancement. The implementation of these strategies has proven effective in strengthening the competitiveness of Kelom Geulis in the market. This study is expected to serve as a practical reference for Kelom Geulis producers to continuously adapt their marketing strategies, ensuring their relevance in the market and appealing to consumers